Effects of Vitamin D on doxorubucin-induced lung injury and TRPM2 immunoreactivity in rats - Yalçın, Alper; Türk, Ahmet; Aydın, Hasan; Yılmaz, Erkan; Çelik, İbrahim Seyfettin; Üçkardeş, Fatih (Journal of Surgery and Medicine, 2020)
Aim: Although doxorubicin (DOX) is a commonly used chemotherapeutic agent, it causes significant toxic side effects on many organs. This study aims to investigate the effects of vitamin D (VD) on DOX-induced lung injury and expression of transient receptor potential melastatin 2 (TRPM2), a Ca2 + permeable cation channel. Methods: A total of 24 Wistar albino rats were separated into four groups of six rats, as follows: The control group received no medications. The VD group received 200 IU/kg VD via an oral dropper (o.d.) for 14-days. DOX group received a single dose of 10 mg/kg DOX intraperitoneally (i.p.) on day 8. DOX+VD group was administered 200 IU/kg VD via an o.d. for 14-days, and a single dose of 10 mg/kg DOX i.p. on day 8. At the end of the experiment, lung and serum samples from all rats were collected. Masson’s trichrome staining and streptavidin-biotin-peroxidase complex were applied to the lung tissue sections. Serum total antioxidant status (TAS) and total oxidant status (TOS) were assessed by enzyme-linked immunosorbent assay (ELISA) method. Results: Histopathological damage was observed in the DOX group compared to the control group, and biochemical and immunohistochemical evaluation revealed that TOS level and TRPM2 expression increased while TAS level decreased significantly (P<0.001). Additionally, compared to the DOX group VD administration significantly reversed these values in the DOX+VD group (P<0.001). Conclusion: VD showed a protective effect on lung damage induced by DOX. Our data also suggest that TRPM2 channel may have a role in the pathophysiology of DOX-induced lung damage.